INTEGRATION MODEL OF CREATIVE TELEMATICS INDUSTRIES WITH MANUFACTURING INDUSTRY IN WEST JAWA PROVINCE - Nurhasan Nurhasan (SAMPURASUN, 2017)
This research is important to integrate the vision and mission of Small and Medium Industries of Creative Telematics with the vision and mission of the Manufacturing Industry especially in West Java province, considering the facts or existing condition that between Small and Medium Industries of Creative Telematics and the Manufacturing Industry still run on their own way and there has not been symbiotic mutualism relations and /or orientation of activities between the two levels of industry has not been integrated. This study was conducted by using empirical juridical approach which is oriented towards holistic study and in the process, legal disciplines receive related disciplines .Analysis of the object of research was conducted through legal analysis The results of this analysis is the drafting of Integration Model Construction of Small and Medium Industries of Creative Telematics in the strengthening of manufacturing industry to increase productivity and competitiveness of industry in west java province, which can be briefly described as follows: a) Intellectual Property Rights produced by Small and Medium Industries of Creative Telematics either Copyrights, Patents, industrial design, or Right to Layout Design of Integrated Circuits is appreciated and is utilized by the specific manufacturing industry, so that both Small and Medium Industries of Creative Telematics and specific manufacturing industry get Added Value to increase the productivity and the competitiveness of local industry and national industry, and periodically Small and Medium Industries of Creative Telematics get the program of technical and management assistance from the specific manufacturing industry in order to meet the standardization of quality of products and quantity of products which is in accordance with standards set by the specific manufacturing industry, and also to gain greater trust from Financial Services to boost the capital; b) the specific manufacturing Industry got efficiency and effectiveness in developing the investments especially related to the fulfillment of the market demands ( design development) and production capacity through symbiotic mutualism and Small and Medium Industries of Creative Telematics; c) The government obtained the holistic study as materials to formulate legislation (Act, government regulations, local regulations) in the field of development of Small and Medium Industries of Creative Telematics in particular, the integrated industrial development and the sustainable industrial development, and the increase of regional revenue in the form of both local taxes and levies. and d) Financial Institutions ( Financial Services ) can reduce or minimize the potency of bad loans from the Small and Medium Industries of Creative Telematics.